2007
DOI: 10.1111/j.1540-8159.2007.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Interference from Wireless Video‐Capsule Endoscopy on Implantable Cardioverter‐Defibrillators

Abstract: In patients with devices identical to those evaluated that showed no interference, the use of the Pill-Cam is safe. However, in patients with a Biotronik Belos ICD (or any other nontested ICD) the use of the Pill-Cam should be done only in-hospital, after suspended ICD therapy and in conjunction with close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…We assessed three cardiac pacemakers and three ICDs manufactured by only two companies, Medtronic (Medtronic, Inc., Minneapolis, MN, USA) and St. Jude Medical (St. Jude Medical, Sylmar, CA, USA). The small number of patients with limited types of cardiac devices observed in this study prevents us from generalizing our results, as EMI differs depending on the device type, manufacturer, and model [17]. However, considering the number of patients with cardiac devices and their general condition, the practical difficulty lies in enrollment of these patients.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We assessed three cardiac pacemakers and three ICDs manufactured by only two companies, Medtronic (Medtronic, Inc., Minneapolis, MN, USA) and St. Jude Medical (St. Jude Medical, Sylmar, CA, USA). The small number of patients with limited types of cardiac devices observed in this study prevents us from generalizing our results, as EMI differs depending on the device type, manufacturer, and model [17]. However, considering the number of patients with cardiac devices and their general condition, the practical difficulty lies in enrollment of these patients.…”
Section: Discussionmentioning
confidence: 83%
“…Filtering technologies to block the outside electric signals differ depending on their manufacturers, as indicated by the results of an in vitro study [17]. Although a unipolar cardiac pacemaker has a different sensitivity to external electromagnetic energy from a bipolar cardiac pacemaker [6,24], electric signals flow into the pacemaker through the telemetry channel rather than the leads, and thus there were no significant differences in interference rates between the two types [8,10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the studies (in VOO, unipolar mode) showed significant interference in the recording when the capsule was near the pacemaker but no change in pacemaker functioning. 15 The other study 16 showed normal function in all ICDs but one (Biotronik Belos ICD). Nonetheless, they recommend suspending ICD therapies in conjunction with close monitoring.…”
Section: Patient Safetymentioning
confidence: 96%
“…14 Nevertheless, they concluded that the use of such technology was safe counting that some precaution measures were taken (e.g., cellular phone in the ipsilateral ear or rapid passing by the antitheft devices). More recently, some authors 15,16 reported interference between video-capsule endoscopy and some IECDs. One of the studies (in VOO, unipolar mode) showed significant interference in the recording when the capsule was near the pacemaker but no change in pacemaker functioning.…”
Section: Patient Safetymentioning
confidence: 98%